The future of business-- annual review 1980/81 : practical issues - Slappey, Sterling G. (Pergamon policy studies., 1980)
The Future of Business-Annual Review 1980/81: Practical Issues is comprised of five essays that examine the opportunities and problems facing business, and their relation to society. The five essays are entitled """"The World of Work Gets Wider and Wilder, """" """"Business Has Failed to Explain Itself, """" """"Changing Demographics and How They Affect the Future of Business, """" """"The Future of Multinational Business, """" and """"Are Material Resources a Restraint on Economic Growth?"""" Gus Tyler's """"The World of Work Gets Wider and Wilder"""" examines the make-up of the constantly expand